INTERTEXTUAL RELATIONS IN METAL FIRTINA 4 TURAN NOVEL METAL FIRTINA 4 TURAN ROMANINDA METİNLERARASI İLİŞKİLER - Mehmet, SOĞUKÖMEROĞULLARI (ASOS Eğitim Bilişim Danışmanlık, 2018)
Tradition is employed in the course of progress of genre of novel, which is introduced to Turkish literature through translations from Western Literature. Especially, the way that Ahmet Mithat Efendi followed provides basis fort he progress of the novel of that kind. In modern thought, corresponding sense of that way is intertextual relations. Briefly, intertextual relations that refer to the gathering and the fashion of redesigning of other texts echo in Metal Fırtına 4 Turan, the subject matter of this study. Metal Fırtına 4 Turan consists of the gathering and reinterpretation of such elements of especially folklore, mythology, and folk literature as Shamanism, Ergenekon epic, wolf, and end of the world or Kalgançı Çak legend. Those elements in the novel constitute the subject matter of this article. Türk edebiyatına Batı edebiyatından çevirilerle giren roman türünün gelişim aşamasında gelenekten faydalanılır. Özellikle Ahmet Mithat Efendi’nin izlediği yol bu yönde romanın ilerlemesine zemin hazırlar. Bu tarzın modern düşüncede karşılığı metinlerarası ilişkilerdir. Kısaca, bir metnin başka metinlerin bir araya gelmesi ve yeniden tasarlanması şeklinde tanımlanabilecek olan metinlerarası ilişkiler, inceleme konumuz olan Metal Fırtına 4 Turan romanına da yansır. Özellikle folklor, mitoloji veya halk edebiyatı ögelerinden Şamanizm, Ergenekon destanı, kurt ve dünyanın sonu veya Kalgançı Çak efsanesinin bir araya getirilerek yeniden yorumlanmasıyla oluşan Metal Fırtına 4 Turan romanındaki bu unsurlar makalenin konusunu teşkil eder.